PKM Pendampingan Guru-Guru SMA Mendesain Dan Menerapkan Pembelajaran Berbasis Blended Learning Di Era Revolusi Industri 4.0 - Motlan; Dedy Husrizal Syah; Jurubahasa Sinuraya; Deo Demonta Panggabean; Mukti Hamjah Harahap; Irfandi (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2020)
The purpose of the activities carried out is to provide: 1). training on learning strategies and innovative learning methods that are fun for students in the form of blended learning, 2). Training and assistance for the preparation of teaching materials, 3). training and assistance in the use of online learning information systems. The approach method in implementing this PKM uses education, training, demonstration, practice, and mentoring methods. The results of the implementation of the activities are: (1) The partner has a school website that can be used as an online learning system under the name SIPO. (2) There is an increase in teacher understanding of the application of blended learning. (3) There is an increase in the understanding of teachers in the preparation of teaching materials themselves. (4) There is an increase in the knowledge and skills of teachers in using the online learning system.